Enhancing Students’ English Communication Skills through Think Pair Share (TPS): A Collaborative Learning Approach in Islamic Higher Education - Nurasia Munir; Sahril Sahril (Lembaga Bale Literasi, 2024)
This study aims to examine the effectiveness of the Think Pair Share (TPS) learning strategy in enhancing English communication skills among second-semester students of the Islamic Communication and Broadcasting (KPI) Department, Faculty of Ushuluddin, Adab and Da’wah, in the English for Communication course. The study employed a quasi-experimental design using a one-group pretest-posttest approach. The participants consisted of 38 students enrolled in the course. Research instruments included speaking performances tests, classroom observation sheets, and student perception questionnaires. Data were collected through pretest and posttests, classroom observations during the implementation of TPS, and questionnaires administered at the end of the intervention. Quantitative data were analyzed using descriptive statistics and paired sample t-tests, while qualitative data were analyzed through thematic interpretation to support the quantitative findings. The result revealed a significant improvement in students’ English communication skills, particularly in speaking fluency, confidence, vocabulary usage, and classroom participation. Students became more actively engaged in discussions and demonstrated greater confidence in expressing their ideas in English. The findings indicate that TPS promotes collaborative learning and provides meaningful opportunities for communication practice. In conclusion, Think Pair Share is an effective instructional strategy for improving English communication skills in Islamic higher education, particularly in English for Specific Purposes (ESP) courses, and is recommended for postering students’ communicative competence and active participation.